The morphological representation of channel-forming flow in arroyos - Ellis, Lucy A. (2004)
This thesis presents a study of three similar, yet contrasting, arroyos: the Rio Puerco, New Mexico and the Santa Cruz and San Simon Rivers in Arizona. Arroyo systems have been subject to several periods of cut and fill within recent geologic time. The most recent incision phase occurred during the mid- to late-19th Century, enabling subsequent morphological changes to be observed. Observations indicate that these systems have developed distinct geomorphological reaches, which evolve at different rates within the constraints of the specific controlling variables, most importantly discharge, sediment load and artificial alteration. Thus, location-for-time substitution cannot be assumed. Within the continuum of morphological change, six stages were identified, enabling a general model of arroyo evolution to be developed.